Technique tip: Simultaneous first metatarsal lengthening and metatarsophalangeal joint fusion for failed hallux valgus surgery with transfer metatarsalgia. Issue 1 (March 2017) - Chowdhary, Ashwin; Drittenbass, Lisca; Stern, Richard; Assal, Mathieu
Highlights: Recurrent hallux valgus may be associated with shortened first metatarsal. Recurrent hallux valgus may be associated with transfer metatarsalgia. Failed hallux valgus surgery may present with degenerated first MTP joint. Fusion of the first MTP joint further shortens the first metatarsal. First metatarsal lengthening along with first MTP joint fusion is described. Abstract: Background: Failed hallux valgus surgery may result in residual or recurrent hallux valgus, and as well transfer metatarsalgia. The present technical tip concerns the combination of fusion of the first metatarsophalangeal (MTP) joint and lengthening of the first metatarsal (MT) through a scarf osteotomy. Materials and Methods: Six patients underwent the presented technique, all for the indication of failed hallux valgus surgery with shortening of the first MT and degenerative changes in the 1st MTP joint. Results: Follow-up at six months revealed all patients had complete healing of the osteotomy and arthrodesis sites. They were all asymptomatic and fully active, completely satisfied with the outcome. Conclusions: Combined fusion of the first MTP joint and lengthening of the first MT through a scarf osteotomy results in an excellent outcome in patients with failed hallux valgus surgery with shortening of the first MT and degenerative changes in the 1st MTP joint.